A comparative on performance of voip using power line and wired (UTP CAT5) / Khainorizan Khalid - Khalid, Khainorizan (Faculty of Information Technology and Quantitative Sciences, 2006)
Power-line networking is one of several ways to connect the computers in home. It uses the electrical wiring in house to create a network. Power-line networking is based on the concept of no new wires. Because it requires no new wiring, and the network adds no cost to electric bill, power-line networking is the cheapest method of connecting computers in different rooms. Small office user and home user (SOHO) have problems in creating a communication medium between them. Besides that, the user needs high-quality internet call with highavailability at low cost. So on this project paper, we would like to do a comparative study on performance of VoIP using Power line and wired (CAT5) to find the best result for creating communication at low cost. So this project paper is want to analysis the performance VoIP using Power line and to compare it with wired .It is testing only in direct LAN. The performance also focuses on measurement of the performance based on packet loss, jitter, delay throughput and bandwidth. Measurement performance on packet loss, jitter and delay is using NetQuality whereas throughput and bandwidth were using NetstatLive. For get the persist result, testing are doing in 15 time for a week for jitter, packet loss and delay.10 time per week for throughput and bandwidth. . The average of the result will compare with performance VoIP using power line and with wired. The conclusion for this comparative the performance communication of the wired performance is better than power line. This is proven from the QoS performances that had been analyzed. It is Analyze quality of voice in more parameter and get the persistence result using the better tools with quality voice, It is recommended to future works not only focused on analysis to Direct LAN. Also focus on analysis the performance at Indirect LAN such as at other block or layer and It is recommended to future works to testing at the other application telephony such as soft phone.